162k views
5 votes
(b) dy/dx = (x - y+ 1)^2

User AnthonyW
by
6.3k points

1 Answer

5 votes

Substitute
v(x)=x-y(x)+1, so that


(\mathrm dv)/(\mathrm dx)=1-(\mathrm dy)/(\mathrm dx)

Then the resulting ODE in
v(x) is separable, with


1-(\mathrm dv)/(\mathrm dx)=v^2\implies(\mathrm dv)/(1-v^2)=\mathrm dx

On the left, we can split into partial fractions:


\frac12\left(\frac1{1-v}+\frac1{1+v}\right)\mathrm dv=\mathrm dx

Integrating both sides gives


\frac+\ln2=x+C


\frac12\ln|1-v^2|=x+C


1-v^2=e^(2x+C)


v=\pm\sqrt{1-Ce^(2x)}

Now solve for
y(x):


x-y+1=\pm\sqrt{1-Ce^(2x)}


\boxed{y=x+1\pm\sqrt{1-Ce^(2x)}}

User Belky
by
6.1k points